Diagnostic performance of mean platelet volume for patients with acute coronary syndrome visiting an emergency department with acute chest pain: the Chinese scenario. Issue 7 (21st July 2010) - Chu, Hsin; Chen, Wei-Lung; Huang, Chien-Cheng; Chang, Hsin-Yu; Kuo, Hung-Yi; Gau, Chorng-Ming; Chang, Yue-Cune; Shen, Ying-Sheng
Abstract : Objectives: To assess the ability of mean platelet volume (MPV) to detect acute coronary syndromes (ACS) in Chinese patients within 4 h of chest pain onset. Methods: Consecutive adult Chinese patients who arrived at an emergency department (ED) with acute chest pain (onset within 4 h) between May and August 2009 were recruited. The MPV was checked for all enrolled patients on arrival at the ED, and further comparisons between the patients in different groups were made. Results: 282 patients (136 men and 146 women) were enrolled and 69 were diagnosed as having ACS (24.5%). As compared with the non-ACS group, the ACS group had significantly higher MPV values (10.8±0.86 fl vs 9.8±0.76 fl, p<0.001). Moreover, we found that the MPV values were higher in patients with acute myocardial infarction (AMI) (n=28) as compared with patients with unstable angina (UA) (n=41) (11.0±0.79 fl vs 10.6±0.87 fl, p=0.027). Multiple logistic regression analysis yielded the fact that the initial MPV was an independent predictor of ACS attack in patients with acute chest pain (OR 8.866). The corresponding area under the receiver operating characteristic curve (ROC) for MPV in predicting ACS in patients with acute chest pain was 0.800 (95% CI 0.736 to 0.864) and the best cut-off value was 10.35 fl (sensitivity 78.3%; specificity 74.6%). Conclusions: MPV is significantly associated with ACS in patients with acute chest pain and is an early and independent predictor.